1993
DOI: 10.1007/bf00586062
|View full text |Cite
|
Sign up to set email alerts
|

Biological monitoring of occupational exposure ton-hexane by measurement of urinary 2,5-hexanedione

Abstract: Occupational exposure to n-hexane in shoe factory workers was monitored by measuring urinary 2,5-hexanedione, the major metabolite of this solvent and the probable cause of peripheral neuropathy in exposed workers. Solvent pollution was monitored in the work environments of 189 employees, of whom 123 (65%) worked in Alicante, Spain, and 66 (35%) in Veneto, Italy. 2,5-Hexanedione was measured in spot urine samples collected from workers at the end of the shift. Information on working conditions was obtained fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 19 publications
0
17
0
2
Order By: Relevance
“…Free 2,5-HD has been evaluated in a limited number of studies and almost always in environments characterized by simultaneous exposure to other solvents 12,23,25,26 . Hamelin et al 27 determined free urinary 2,5-HD excretion and HEX in alveolar air in five volunteers exposed to HEX (25-50 ppm) for 5 consecutive days and concluded that both free urinary 2,5-HD and HEX in alveolar air are adequate indicators in the biomonitoring of exposure to HEX.…”
Section: Resultsmentioning
confidence: 99%
“…Free 2,5-HD has been evaluated in a limited number of studies and almost always in environments characterized by simultaneous exposure to other solvents 12,23,25,26 . Hamelin et al 27 determined free urinary 2,5-HD excretion and HEX in alveolar air in five volunteers exposed to HEX (25-50 ppm) for 5 consecutive days and concluded that both free urinary 2,5-HD and HEX in alveolar air are adequate indicators in the biomonitoring of exposure to HEX.…”
Section: Resultsmentioning
confidence: 99%
“…The risk of exposure can be gauged by monitoring ambient air levels [ 83 ] . Urinary measurement of 2,5 hexanedione may allow detection of exposure prior to the appearance of signi fi cant toxicity [ 84 ] . The only available treatment is cessation of hexacarbon exposure.…”
Section: Treatment and Managementmentioning
confidence: 99%
“…In patients with clearly established neuropathy, all the above changes became much more pronounced, and marked decreases in MCV and SCV and obvious prolongation of distal and F-wave latencies (DL) also occur 2,4,5) , suggesting that the primary neurotoxic effect of 2,5-hexanedione (2,5-HD) is axonal with secondary demyelination 7,11) . The neurotoxic effects of HEX are related to 2,5-HD 11,15) , an active γ -diketone that is the only neurotoxic metabolite of HEX. Recent studies have shown that axon atrophy is the morphological hallmark of γ -diketone neuropathy 16,17) and that regardless of exposure rate (100−400 mg/kg/day), it is an early consequence of 2,5-HD neurotoxicity and a necessary event in the pathophysiological process that leads to γ -diketone neurological toxicity 18) .…”
Section: Abstract : a S Y M P T O M A T I C S H O E M A K E R S mentioning
confidence: 99%